New Rice (Oryza sativa L.) demonstration and popularization in Pawe district, Metekel zone, North Western Ethiopia - Tafere Mulualem Emrey; Desta Abebe Belete (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Rice is one of the millennium crops that give more attention by the government of Ethiopia to bring food security across the nation. Research has been conducted on rice and released promising rice varieties by Pawe agricultural research center in collaboration with Adet agricultural research center in the past. The objective of this demonstration was to popularize and demonstrate the newly released rice variety i.e. PSBRC92 and to get feedback from the end-users. In the field demonstration, a total of 50 rice producer farmers participated and they have given their own suggestions concerning the new rice variety compared with the check one. The advantages of using the new rice variety over the standard check are early maturity and high quality of resistance to diseases. Farmers' agricultural experts and researchers were discussed fruitfully. Finally, farmers showed their interest to use the new rice variety, if they have got access to get the seed. Generally, all the stakeholders have agreed to do more to maximize and popularization of the new rice variety and the paper will provide some information to the readers about rice variety development research in Pawe as well as in Ethiopia.